Citra Teruna-Teruni Bali dari Aspek Sosiologis dalam Novel "Sukreni Gadis Bali" Karya Pandji Tisna - I Wayan Nitayadya (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Issues examined in this study is how the image of youth-teruni Bali of the sociological aspects of the novel Sukreni Girl Bali. The method used in the data menganalisis is descriptive analytic method. The aim was to obtain an overview of image-teruni cadet Bali in Bali Girl Sukreni novel of the sociological aspects. The result of this analysis of the image of youth-teruni Bali in conjunction with another character in person is the image of the submissive teruni to parents, teruni a double love, the image of youth that promotes friendship, the image of youth who tried to resuscitate the elderly, and youth who rebel against their parents, while the image of youth-teruni Bali in relation to society is touth-image teruni responsible for customs and disturbing the public image of a cadet.